THE PECULIARITIES OF THERMAL INDUCEMENT VENTILATION SYSTEMS - D. V. Abramkina (Вестник СибАДИ)
Introduction. For increasing the efficiency of natural ventilation systems, it is possible to use the thermal incentives - additional heating of the exhaust  ventilation duct, which allows to expand temperature difference between  ambient and exhaust air and to increase the circulation effect. This method  enables stable air exchange in hot period, independently of the wind  direction force. However, existing systems have several limitations of  application in the high-rise apartment building in countries with a cold climate. The aim of the study is to develop a thermal inducement  ventilation systems, suitable for typical residential apartment buildings in russian climate.Results. The article theoretically proves the disadvantages of existing thermal inducement ventilation systems. The article also presents the results  of numerical modeling of natural convection currents in the high-rise  apartment building. The dependence of outlet velocity on temperature  difference for various heating methods is proved on the basis of the research.Conclusion. The results of the research illustrate the high level of the heating area location influence on free convection currents in vent duct.